2021
DOI: 10.1007/s40123-021-00385-8
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of Life in Patients with Chronic Thyroid Eye Disease in the United States

Abstract: Introduction: Thyroid eye disease (TED) is an autoimmune condition producing ocular pain, dysmotility, and ocular structure and function changes. As disease activity changes, redness, swelling, and pain can improve, but eye comfort, appearance, and motility alterations often persist. There are limited data on chronic TED

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
(61 reference statements)
1
30
0
1
Order By: Relevance
“…2) ( 22) was used to preprocess the rsfMRI data, which is based on SPM12 (http://www.fil.ion.ucl.ac.uk/spm/software/spm12) (23). The main processes were as follows: (1) the first ten volumes of each data were removed to reduce the influence of machine instability and subject adaptation to the environment; (2) slice timing correction was performed on the data of the remaining 230 time points; (3) realignment for head motion correction; (4) the realigned functional images were normalized to the Montreal Neurological Institute template by using T1 image unified segmentation; (5) and then the functional images were resampled to 3 × 3 × 3 mm 3 voxel; (6) detrending was conducted to remove linear trend; (7) the Friston 6-parameter model, cerebrospinal fluid, and white matter were regressed as covariates in MNI space; (8) bandpass filtering (based on frequency 0.01-0.08 Hz) was performed to reduce the effects of low frequency drift and high frequency noise. The whole dataset of this subject would be abandoned, if the maximum value of the head translation (rotation) movement was more than 2.0 mm (2.0 • ).…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) ( 22) was used to preprocess the rsfMRI data, which is based on SPM12 (http://www.fil.ion.ucl.ac.uk/spm/software/spm12) (23). The main processes were as follows: (1) the first ten volumes of each data were removed to reduce the influence of machine instability and subject adaptation to the environment; (2) slice timing correction was performed on the data of the remaining 230 time points; (3) realignment for head motion correction; (4) the realigned functional images were normalized to the Montreal Neurological Institute template by using T1 image unified segmentation; (5) and then the functional images were resampled to 3 × 3 × 3 mm 3 voxel; (6) detrending was conducted to remove linear trend; (7) the Friston 6-parameter model, cerebrospinal fluid, and white matter were regressed as covariates in MNI space; (8) bandpass filtering (based on frequency 0.01-0.08 Hz) was performed to reduce the effects of low frequency drift and high frequency noise. The whole dataset of this subject would be abandoned, if the maximum value of the head translation (rotation) movement was more than 2.0 mm (2.0 • ).…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
“…Despite that TAO patients commonly complain about the ocular symptoms ( 3 ), the additional psychological and psychiatric disturbances can also markedly reduce the patients' quality of life ( 4 ). Specifically, cognitive function such as performing daily work and maintaining social relationships ( 5 ), and emotion regulation ability such as relieving depression and anxiety ( 6 ) have been reported to be impaired. A prior cohort study even showed a higher suicidal tendency for TAO patients ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Discriminant validity describes the ability of an instrument to distinguish between qualitatively different disease states. Each of the TED-specific instruments does appear to demonstrate reasonable discriminant ability having been tested across disease severity states ( 5 , 22 , 31 , 33 , 36 , 47 , 52 , 53 , 60 ) and over the course of treatment ( 9 , 10 , 18 , 37 , 40 , 41 , 43-45 ).…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…Eye conditions and vision impairments are associated with many negative consequences such as vision loss, psychological distress, impaired everyday functioning, social isolation and loneliness, uncertainty in illness, and deteriorated socioeconomic status; therefore, compared to normally-sighted persons, persons with eye conditions and vision impairments are more likely to develop mental health problems, in particular depression (1,(6)(7)(8)(9)(10). For example, the prevalence rates of depressive symptoms in middle-aged and older adults with glaucoma, patients with cataracts, patients attending eye clinics, patients with chronic thyroid eye disease, patients with legal blindness, attendees at low-vision rehabilitation centers, and patients with dry eye disease are 10.9, 23.9, 25.0, 28.0, 29.0, 43.0, and 61.0%, respectively (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, diagnostic interview-based assessment findings are more clinically relevant than self-report-based assessment findings. Because nearly all existing studies assessed depression in persons with eye conditions and vision impairments by using self-report scales (11)(12)(13)(14)(15)(16)(17), one significant limitation of prior studies is the limited clinical significance of their assessments of depression. In addition, the other significant limitation of previous studies is the potential selection bias in samples of persons with eye conditions and impairments, since samples of most available studies were recruited from clinical settings (6, 12-14, 16, 17).…”
Section: Introductionmentioning
confidence: 99%